Preparation and characterization of mullite-based ceramics from Malaysian kaolin - Choo, Thye Foo (2012)
Mullite ceramics are high performance ceramic due to its excellent high thermal shock resistance, chemical attack resistance, high hot strength and creep resistance properties. However, economical concerns in terms of cost and availability of mullite‘s raw materials have brought current efforts toward development of new inexpensive raw materials to synthesis mullite. The first study investigates the effect of aluminum leaching during iron removal from kaolin to mullite. Heat-treated kaolin was obtained by heating natural kaolin at 400, 500, 600, 700, 800 and 900 °C. The heat-treated kaolin was then leached at 100 °C with 4 M, 3 M, 2 M, 1 M, 0.2 M solution of sulfuric acid and 0.2 M solution of oxalic acid. The dried samples were sintered to 1300 °C for 4 hour at a heating rate of 10 °C min−1. X-ray diffractometry and differential thermal analysis were used to study the phase transformation of kaolin to mullite. It was found that 700 °C is the optimum preheat-treatment temperature to leach out iron and also aluminum for both types of the acids used. The majority of the 4 M sulfuric acid-treated kaolins formed the cristobalite phase when sintered. On the other hand, 1 M, 0.2 M sulfuric acid and 0.2 M oxalic acid leached heat-treated kaolin formed mullite and quartz phase after sintering. Another study has been conducted to look into the possibility of using Malaysian kaolin and aluminum hydroxide to synthesize mullite. The treated Malaysian kaolin is mixed with aluminum hydroxide accordingly with the percentage of 10 %, 20 %, 30 %, 40 %, 50 %, 60 % and 80 % by weight. The study focuses on the effects of additional aluminum hydroxide on phase transformation of acid leached metakaolin clay. Finally, the percentage of mullite in the samples is compared with the percentage of aluminum hydroxide added. The results show that percentage of mullite in the treated kaolin can be increased by introducing additional of aluminum hydroxide. It was found that a correlation between percentage of aluminum hydroxide added and percentage of mullite formed can be established with a general equation. The study also reveals that the length of the acicular shape mullite crystals can be elongated from 2 up to 20 microns as the firing temperature increase from 1300 to 1600oC.